2022
DOI: 10.3390/agriculture12081192
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional Neural Networks in Detection of Plant Leaf Diseases: A Review

Abstract: Rapid improvements in deep learning (DL) techniques have made it possible to detect and recognize objects from images. DL approaches have recently entered various agricultural and farming applications after being successfully employed in various fields. Automatic identification of plant diseases can help farmers manage their crops more effectively, resulting in higher yields. Detecting plant disease in crops using images is an intrinsically difficult task. In addition to their detection, individual species ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(36 citation statements)
references
References 120 publications
0
34
0
2
Order By: Relevance
“…Neural networks with two or more layers are the conceptual basis to generate DL models, whose progress has been spectacular in recent years in all disciplines, even in precision crop protection ( Ferentinos, 2018 ; Kamilaris and Prenafeta-Boldú, 2018 ; Xia et al., 2018 ; Farooq et al., 2019 ; Hasan et al., 2021 ; Rakhmatulin et al., 2021 ; Allmendinger et al., 2022 ; Tugrul et al., 2022 ; Rai et al., 2023 ). DL algorithms transform data to construct complex concepts in a hierarchical structure with several levels of abstraction, so that the higher levels are composed of the characteristics of the lower levels ( LeCun et al., 2015 ).…”
Section: Taxonomy Based On the Tasks To Be Solvedmentioning
confidence: 99%
“…Neural networks with two or more layers are the conceptual basis to generate DL models, whose progress has been spectacular in recent years in all disciplines, even in precision crop protection ( Ferentinos, 2018 ; Kamilaris and Prenafeta-Boldú, 2018 ; Xia et al., 2018 ; Farooq et al., 2019 ; Hasan et al., 2021 ; Rakhmatulin et al., 2021 ; Allmendinger et al., 2022 ; Tugrul et al., 2022 ; Rai et al., 2023 ). DL algorithms transform data to construct complex concepts in a hierarchical structure with several levels of abstraction, so that the higher levels are composed of the characteristics of the lower levels ( LeCun et al., 2015 ).…”
Section: Taxonomy Based On the Tasks To Be Solvedmentioning
confidence: 99%
“…The models are developed with deep, complex, and high parameters to achieve high accuracy with a limitation of complex computation. VGGNet, InceptionV3, AlexNet, GoogLeNet, and XceptionNet are widely used DL models [144]. Some models are developed to achieve computation efficiency with a restriction of adequate accuracy.…”
Section: Analysis Of Various Classification Approachesmentioning
confidence: 99%
“…Using a mix of a Deep Learning classification model (CNN) and a features selection method genetic algorithm (GA), a model is presented for the diagnosis and recognition of tomato plant disease using the leaf image data ( Tugrul et al., 2022 ). The proposed given framework was trained on 500 images belonging to 4 types of diseases.…”
Section: Related Workmentioning
confidence: 99%
“…According to the Ministry of Food Processing Industries, agricultural losses in 2016 totaled thirteen billion US dollars ( GoI, 2019 ). Image processing and neural networks can be used to perform one of the beneficial steps in plant disease diagnosis techniques ( Tugrul et al., 2022 ). Recent research has demonstrated that neural networks and deep learning perform categorization tasks effectively.…”
Section: Introductionmentioning
confidence: 99%